2021
DOI: 10.3390/app11031158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Internal Structure of the Sorbents on Diazepam Sorption from Simulated Intestinal Fluid

Abstract: The capacity of natural Na-montmorillonite and activated charcoal for sorption of diazepam from simulated intestinal fluid (SIF) was studied. The main characteristics of the sorbents were determined. In order to characterize the sorption process of diazepam the influence of the pH, contact time and ethanol presence in SIF was analyzed. Adsorption isotherms for the diazepam-activated charcoal and diazepam-natural Na-montmorillonite systems were determined. The Langmuir isotherm model provided a very good descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…have studied the influence of internal structure of the adsorbents on diazepam adsorption in simulated intestinal fluid (SIF) and reported the higher adsorption capacity of activated carbon than mineral clay since the activated carbon has a pore volume which is much higher than the one of the mineral clay. Another important result is the uptake of diazepam by both adsorbents decreases in the presence of ethanol 4 . Regmi et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…have studied the influence of internal structure of the adsorbents on diazepam adsorption in simulated intestinal fluid (SIF) and reported the higher adsorption capacity of activated carbon than mineral clay since the activated carbon has a pore volume which is much higher than the one of the mineral clay. Another important result is the uptake of diazepam by both adsorbents decreases in the presence of ethanol 4 . Regmi et al.…”
Section: Introductionmentioning
confidence: 98%
“…Another important result is the uptake of diazepam by both adsorbents decreases in the presence of ethanol. 4 Regmi et al have reported in vitro adsorption of dextromethorphan syrup which is an over-the-counter antitussive drug using activated charcoal in simulated gastric and intestinal fluids. They have showed that the use of activated charcoal might be the most effective approach for the dextromethorphan overdose treatment.…”
Section: Introductionmentioning
confidence: 99%